Pemahaman Finansial dalam Mempersiapkan Generasi Muda Mandiri di Labuan Bajo - Ludgardis Deliman; Priska Yuliani; Elisabet Oktaviani Hanggu (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
Financial literacy is an important skill needed to prepare the young generation to be independent, especially in areas with great economic potential such as Labuan Bajo. This study aims to explore the level of financial literacy of the young generation, the challenges they face, and strategies to increase their economic independence. Using qualitative methods, data were collected through in-depth interviews, focus group discussions (FGDs), and participant observation of the young generation, educators, and local business actors. The results of the study indicate that the financial literacy of the young generation in Labuan Bajo is still limited, especially in the aspects of long-term financial planning and investment. The main obstacles faced include lack of access to financial education, consumer culture, and the lack of relevant financial literacy programs. However, there is great potential to improve financial literacy through community-based programs, integration of financial materials into the education curriculum, and practical training involving local economic actors. This study concludes that improving the financial literacy of the young generation in Labuan Bajo requires collaboration between various parties, including the government, educational institutions, and local communities. With a planned strategy, financial literacy can be the foundation for building a more independent young generation, ready to face global economic challenges, and able to take advantage of local opportunities. These findings provide concrete recommendations for the development of financial literacy programs that are relevant to the needs of the community in Labuan Bajo.